Morphometic cadaveric analysis of thyroid cartilage in Indian adults with comparative review of studies on other ethnic population - Sahoo, Satyanjaya; Mallick, Ajay; Sethi, Ashwani; Joshi, Himanshu; Ghotra, Aroma (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The larynx besides being used in respiration, performs the function of production of voice. A thorough knowledge of relevant surgical anatomy is a must for any surgeon before performing laryngeal framework surgery (LFS). Most of the relevant anatomic details for LFS are based on Western population and the studies based on Indian population are extremely scarce. We propose to undertake this study in order to understand the relevant anatomy of the thyroid cartilage in adult Indian population and to compare these dimensions with those studied in the western population as available in literature. Methods: Fifty-two samples of adult thyroid cartilage (35 males and 17 females) taken from cadavers were analysed. Digital Vernier callipers & goniometer were used to take morphometric measurements of the Thyroid cartilage to see for normal variation, sex differences and bilateral asymmetry. Observation were analysed by calculating mean & SD. Results: Most parameters measured in thyroid cartilage did not show significant difference in males & females. All the parameters of thyroid cartilage except thyroid angle were higher in males than females. Bilateral asymmetry in the size of thyroid lamina was seen in majority of specimens though not statistically significant. Conclusions: The detailed study of thyroid cartilage in the form of morphometric parameters of thyroid cartilage is useful for anatomists, radiologists, reconstructive and ENT surgeons. Comparison with other populations in the world reveals that the absolute values differ in different populations which could be due to differences in body built, racial differences and age group of cadavers.